Find the sum 1 2 + ( 1 2 + 2 2 ) + ( 1 2 + 2 2 + 3 2 ) + ⋯ + ( 1 2 + 2 2 + ⋯ + 1 0 0 0 2 )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
the sum will be "a sigma of sigmas"
the nth term will beUn = ∑n² = n(n+1)(2n+1)/6
S(n) = ∑Un = ∑n(n+1)(2n+1)/6 = n(n+1)²(n+2)/12
S(1000) = 83666083500
S = 1 2 + ( 1 2 + 2 2 ) + ( 1 2 + 2 2 + 3 2 ) + ⋯ + ( 1 2 + 2 2 + ⋯ + 1 0 0 0 2 ) = 1 0 0 0 × 1 2 + 9 9 9 × 2 2 + 9 9 8 × 3 2 + ⋯ + 1 × 1 0 0 0 2 = n = 1 ∑ 1 0 0 0 ( 1 0 0 1 − n ) n 2 = 1 0 0 1 n = 1 ∑ 1 0 0 0 n 2 − n = 1 ∑ 1 0 0 0 n 3 = 1 0 0 1 × 6 1 0 0 0 ( 1 0 0 1 ) ( 2 0 0 1 ) − ( 2 1 0 0 0 ( 1 0 0 1 ) ) 2 = 8 3 6 6 7 0 8 3 5 0 0
Problem Loading...
Note Loading...
Set Loading...
The i t h term of the series is 1 2 + 2 2 + 3 2 + . . . + i 2 = 6 2 i 3 + 3 i 2 + i . So S n = sum of first n terms of the series is 1 2 n ( n + 1 ) 2 ( n + 2 ) . Therefore the sum of the first 1 0 0 0 terms is 8 3 6 6 7 0 8 3 5 0 0